Groundwater Distribution and Potency in Faculty of Mathematics Natural Sciences, Universitas Jember based 3-Dimensional Resistivity Data Modelling - Sari, Herlina Putri; Suprianto, Agus; Priyantari, Nurul (BERKALA SAINSTEK, 2022)
Lack of clean water when entering the dry season is a problem that often occurs in the FMIPA University of Jember. The purpose of this research is to know and estimate the potential distribution of the aquifer in the research area. 3D modeling of resistivity data was carried out using Voxler software. The input of resistivity data from the measurement results in the research area that the inversion process had carried out. The modeling results obtained an aquifer potency of 207.862,21 m3 or 21.63% of the total volume on the model image's cross-sectional map, with an irregular distribution pattern. Finally, using this method, the modeling of the aquifer potential volume and distribution can be estimated, and can be used as consideration in the use of groundwater in the Faculty of Mathematics and Natural Sciences, University of Jember.